KAWASAN LAR DI KABUPATEN SUMBAWA - , HILAL ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Society in Sumbawa regency, Indonesia, has a tradition of farming in lar . This farming tradition is a habit that has been attached in the community a long time and practiced from generation to generation. As known, Sumbawa people has husbandry tradition that can not be separated with their farming tradition in their daily life. Communities deal with natural conditions are sensitively using cistern rain system of agriculture since this humid tropical climate condition, there are so many pastures ( lar ) exist. When the rainy season / planting season comes , people first take their livestock to the lar, so basiru system activities is able to deliver properly. In addition, it also keeps farming from an interference of their animals. Using lar as a grazing area with communities which relies on social consensus has begun in danger. This condition influenced by a faster development of human civilization including some adjustments. Changes in agriculture tradition which is highly associated with husbandry traditions give a strong influence in their practical breeding system. The purpose of this study was to describe the concept of space-based on traditional values of Sumbawa community in the lar managemet. This research was deductive and using qualitative methods through phenomenological approach . Results of this study found that the tradition of farming and husbandry are the two activities that complimentary each other . First , the tradition of farming with the basiru patterns has been involved in the establisment of husbadry tradition using lar area. Second, the community awares that removing livestock within lar sytem has some consequences, for instance the livestocks leave the lar area to the farming area. To handle these problems, the communities have tried to make fence to protect their farming area from the livestocks. Some spatial patterns in the lar area emerge from these phenomena. Third, the lar area as raising area is managed together based an a social consensus and so far it is still running well without any individual interest an it. Fourth